Development of Canva Flash Based Mathematics Learning Media on Matrix Material - Malik, Fatus Atho'ul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
Utilization of technology-based media in learning can build student independence so that the student learning experience will have more meaning. This research is aresearch on the development of mathematics learning media. The purpose of this research is to develop a valid and practical Canva Flash Matrix-based mathematics learning media as a mathematics learning medium on matrix material. The method in this study uses a development method based on the ADDIE development model. The subjects used in this study were 20 students of class XI MA Ibadurrochman. The resulting learning media is Canva-based media for material on the Matrix with a discussion of the types of Matrix and operations on the Matrix. Research data were analyzed using descriptive statistical analysis. The data that has been obtained is then analyzed using validation analysis techniques, practicality, developed learning media. The results of the validation test and practicality test resulted in a valid and practical mathematics learning media to be used as a medium in learning based on the results of an assessment that met the criteria. The results of the assessment from the validation of media experts showed an average total score of 3.78. This shows that the media is valid for use in learning. In addition, the media also meets practical standards with an average practicality score of 3.70. Thus, the developed Flash Matrix media fulfills valid and practical aspects. Research also shows that the media can make students play an active role in observing the material presented, so that it can help teachers in the learning process and learning more effectively.